ANALISIS SISTEM PENCATATAN LAPORAN KEUANGAN MANUAL - Hania Lailatul Rahmalia; Fitri Komariyah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine the recording of the financial statements of PT. Rumah Sehat Naily which applies the manual method. In this research, there are several types that are carried out, namely using descriptive, observation and interview methods. Where the company only uses a simple recording or accounting cycle that can only be understood by the company PT. Rumah Sehat Naily. So that the system of recording financial statements at PT. Rumah Sehat Naily needs a more adequate system to improve the quality of records to be more effective and efficient in the sense that financial reports can be prepared and completed in a timely manner